2014
DOI: 10.1107/s139900471401606x
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the substrate selectivity of PvuRts1I, a 5-hydroxymethylcytosine DNA restriction endonuclease

Abstract: The crystal structure of PvuRts1I was determined and a 5-hydroxymethylcytosine-binding pocket was identified in the SRA-like domain. Enzyme variants were engineered to assist in hydroxymethylome mapping based on the crystal structure of PvuRts1I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…The cyanide groups in (I) adopt only a bidentate bridged geometry. The bridged C1-N1 distance of 1.142 (6) Å is typical for a cyanide C N bond length (Jia & Hou, 2012;Meng et al, 2012;Shao & Yu, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The cyanide groups in (I) adopt only a bidentate bridged geometry. The bridged C1-N1 distance of 1.142 (6) Å is typical for a cyanide C N bond length (Jia & Hou, 2012;Meng et al, 2012;Shao & Yu, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These include MspJI, which recognizes 5mC and 5hmC (20), the PvuRts1I family, whose members show unique individual specificities for 5hmC and/or 5-glucosylhydroxymethylcytosine (5ghmC) (21), and GmrSD, which recognizes 5ghmC (22). Structural studies of McrB, MspJI, PvuRtsI, and AbaSI suggest type IV systems employ a generalized base-flipping mechanism for recognition of the modified DNA (23)(24)(25)(26)(27).…”
Section: This Work Was Supported By Cornell University and National Imentioning
confidence: 99%
“…Mutational analysis and close structural resemblance of DNA binding domains of AspBHI, PvuRts1I and AbaSI to the SRA domains of MspJI and eukaryotic proteins ( Fig. 1C-D ) suggest that these enzymes also flip-out the modified cytosine [18] , [20] [23] .…”
Section: Introductionmentioning
confidence: 96%
“…Due to strict specificity for unmodified DNA and fixed cleavage positions, both MspJI- and PvuRts1I-like enzymes are used as molecular tools for single-base resolution mapping of 5mC and 5hmC modifications in eukaryotic genomes [16] , [17] . The recently solved structures of MspJI, AspBHI (MspJI family), PvuRts1I and AbaSI (PvuRts1I family) enzymes [18] [23] revealed that these enzymes are comprised of a PD-(D/E)XK nuclease domain fused to a SRA-like DNA binding domain (DBD). The co-crystal structure of the MspJI-DNA complex demonstrated that MspJI flips-out 5-methylcytosine into a protein pocket where a set of base-specific contacts are made ( Fig.…”
Section: Introductionmentioning
confidence: 99%